EULAR/PReS standards and recommendations for the transitional care of young people with juvenile-onset rheumatic diseases. Issue 4 (1st November 2016) - Foster, Helen E; Minden, Kirsten; Clemente, Daniel; Leon, Leticia; McDonagh, Janet E; Kamphuis, Sylvia; Berggren, Karin; van Pelt, Philomine; Wouters, Carine; Waite-Jones, Jennifer; Tattersall, Rachel; Wyllie, Ruth; et al.
Abstract : To develop standards and recommendations for transitional care for young people (YP) with juvenile-onset rheumatic and musculoskeletal diseases (jRMD). The consensus process involved the following: (1) establishing an international expert panel to include patients and representatives from multidisciplinary teams in adult and paediatric rheumatology; (2) a systematic review of published models of transitional care in jRMDs, potential standards and recommendations, strategies for implementation and tools to evaluate services and outcomes; (3) setting the framework, developing the process map and generating a first draft of standards and recommendations; (4) further iteration of recommendations; (5) establishing consensus recommendations with Delphi methodology and (6) establishing standards and quality indicators. The final consensus derived 12 specific recommendations for YP with jRMD focused on transitional care. These included: high-quality, multidisciplinary care starting in early adolescence; the integral role of a transition co-ordinator; transition policies and protocols; efficient communications; transfer documentation; an open electronic-based platform to access resources; appropriate training for paediatric and adult healthcare teams; secure funding to continue treatments and services into adult rheumatology and the need for increased evidence to inform best practice. These consensus-based recommendations inform strategies to reach optimal outcomes in transitional care for YP with jRMD based on available evidence and expert opinion. They need to be implemented in the context of individual countries, healthcare systems and regulatory frameworks.